2019
DOI: 10.1136/bmjopen-2019-029850
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic, non-specific low back pain on superficial lumbar muscle activity: a protocol for a systematic review and meta-analysis

Abstract: IntroductionChronic, non-specific low back pain is a major global cause of disability. One factor which might potentially contribute to ongoing pain is maladaptive variation in the level of activity in the lumbar musculature. Several studies have investigated this activity using surface electromyography, in varied muscles and during a number of functional activities. Due to differences in the applied methodology, the results have been difficult to compare, and previous reviews have been limited in scope. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…There are studies in the literature arguing that the reduction in lumbar curvature is correlated with lower back pain (26). Although studies in the literature have reported that extensor muscles of patients with lower back pain are smaller compared to those of healthy volunteers (12,16), in the present study all participants were the patients with lower back pains, and when sagittal curvature angles and lower lumbar extensor muscle volumes were evaluated between these patients themselves, as is expected muscle volumes were greater in the patients with a larger curvature.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…There are studies in the literature arguing that the reduction in lumbar curvature is correlated with lower back pain (26). Although studies in the literature have reported that extensor muscles of patients with lower back pain are smaller compared to those of healthy volunteers (12,16), in the present study all participants were the patients with lower back pains, and when sagittal curvature angles and lower lumbar extensor muscle volumes were evaluated between these patients themselves, as is expected muscle volumes were greater in the patients with a larger curvature.…”
Section: Discussionmentioning
confidence: 72%
“…A greater muscle strength is needed to provide stability of lumbar vertebrae with a greater curvature, and force-generating capacity of a muscle is associated with the physical size of the muscle. This suggests variations in the size of the extensor muscle (15,16). This variation has been reported to be associated with the variation in lumbar curvature (17).…”
Section: Discussionmentioning
confidence: 80%
“…If there are discrepancies between the two reviewers on inclusion of certain studies in the meta-analysis or subgroup analysis, or whether or not to conduct the meta-analysis at all, then a third reviewer (DF) will determine the potential for meta-analysis. 34 …”
Section: Study Recordsmentioning
confidence: 99%
“…29 35 Similar to previous reviews, we will proceed with meta-analysis if the I 2 value is <50%. 34 36 …”
Section: Study Recordsmentioning
confidence: 99%
See 1 more Smart Citation